PERANCANGAN E-VOTING BERBASIS SMART CONTRACT MENGGUNAKAN KEAMANAN ALGORITMA KONSENSUS PROOF-OF-STAKE - Lase, Adi Gunawan; Putri Pratiwi, Mariska (Computer Science and Industrial Engineering, 2024)
The advancement of digital technology has created opportunities for efficiency in voting processes through e-voting system. However, the conventional e-voting systems are often vulnerable to cyber attacks and data manipulation. The main issue lies in the centralized architecture of these systems, which present significant security risks. This study explores the implementation of a more secured e-voting system built on blockchain technology, utilizing smart contracts on the Ethereum platform, that leverages the Proof-of-stake consensus with specific focus on vendor selection. By utilizing a decentralized architecture, the blockchain-based system eliminates single points of failure and distributes data across multiple nodes, significantly reducing the risk of manipulation or unauthorized access. This research concludes that the implementation of blockchain technology, especially that leverages the PoS consensus algorithm and smart contract on the Ethereum platform, can perform effectively and provide enhanced security compared to conventional e-voting systems.